Studi Makna dan Ruang dalam Hunian Tradisional Manggarai, Flores Nusa Tenggara Timur - Terisno, Visensisus Herdy; Tulistyantoro, Lintu; Nilasari, Poppy Firtatwentyna (Intra, 2019)
The form of archipelago architectural dwelling has many values and meanings contained. This is because there is a relationship between meaning and space. The Manggarai community has a picture of occupancy that has enormous value and meaning. This is confirmed by the belief in spiritual values in the form of the ancestral grave (Compang) in the middle of the village. Graves are symbolic expressions of the existence of their ancestors. The method used in this study is qualitative by conducting observations, documentation and interviews. Then in analyzing the data, using a comparative method with other traditional occupancy but still in one cognate. The form of cosmology of the manggarai community is expressed in its dwelling, this is integrated with the dualism understanding found